Effectiveness of offline and online learning during COVID-19 pandemic: Two-factor analysis of variant approach in S-1 Students of FKIP University PGRI Banyuwangi, Indonesia - Najib, Moch.; Mursidi, Agus (Linguistics and Culture Review, 2021)
This study aims to determine the effectiveness of offline learning and online learning with a two-factor analysis of variance approach. The subjects in this study were undergraduate students of FKIP PGRI Banyuwangi University from the history education study program. method Quasi Experimental Design which has two groups, namely online and offline, which cannot fully function to control external variables that can affect the experiment. The population of this research is the students of the Faculty of Teacher Training and Education as many as 132 students. Based on the results of the two-way ANOVA test, a significance result of 0.056> from 0.05 was obtained, it can be concluded that there is no difference between Learning Effectiveness based on study programs at the teaching and education faculty at PGRI Banyuwangi University. but if seen from the results of the significance of 0.00 <0.05, it can be concluded that there is a difference between the effectiveness of learning based on teaching methods in the faculty of teacher training and education science at the PGRI Banyuwangi university.